2023
DOI: 10.1001/jama.2023.5942
|View full text |Cite
|
Sign up to set email alerts
|

Global Variations in Heart Failure Etiology, Management, and Outcomes

Abstract: ImportanceMost epidemiological studies of heart failure (HF) have been conducted in high-income countries with limited comparable data from middle- or low-income countries.ObjectiveTo examine differences in HF etiology, treatment, and outcomes between groups of countries at different levels of economic development.Design, Setting, and ParticipantsMultinational HF registry of 23 341 participants in 40 high-income, upper–middle-income, lower–middle-income, and low-income countries, followed up for a median perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In Reply We thank Dr Entezari-Maleki for interest in our article . Two large trials of statins have demonstrated no benefit in people with heart failure .…”
mentioning
confidence: 95%
“…In Reply We thank Dr Entezari-Maleki for interest in our article . Two large trials of statins have demonstrated no benefit in people with heart failure .…”
mentioning
confidence: 95%
“…In the Original Investigation titled “Global Variations in Heart Failure Etiology, Management, and Outcomes,” published in the May 16, 2023, issue of JAMA , errors in the article text and online supplements occurred. On page 1654, in the “Thirty-Day Case-Fatality Rate After the First Hospitalization Occurring in Follow-up” subsection of the Results, the first sentence should have read “Unadjusted 30-day case fatality after the first hospital admission date was lowest in high-income countries (6.7%), but case fatality increased as country income level decreased….” In the Conflict of Interest section, the surname should have been spelled as Yusuf for Salim Yusuf, DPhil.…”
mentioning
confidence: 99%
“…To the Editor The Global Congestive Heart Failure (G-CHF) Investigators recently published a landmark study on global variations in heart failure etiology, management, and outcomes among 23 341 participants from 40 countries across 4 income levels. They showed that patients with heart failure in low-income and lower-middle-income countries had a higher risk of death and were less likely to be prescribed heart failure therapies that improve survival compared with participants in high-income countries.…”
mentioning
confidence: 99%
“…Similar recommendations come from the 2013 American College of Cardiology/American Heart Association guideline on the treatment of blood cholesterol to reduce atherosclerotic cardiovascular risk in adults and the later 2018 update recommending a statin for adults (≥21 years of age) with atherosclerotic CVD and for individuals aged 40 to 75 years with diabetes. Therefore, considering that the G-CHF registry enrolled participants from 2016 to 2020, and a substantial proportion of these patients had CVD risk factors, including ischemic heart disease (38.1%), diabetes (30.9%), hypertension (65.7%), and smoking (8.4%), it is likely that many would have met criteria for statin use. SGLT2 inhibitors are another class of medication that improve survival in people with heart failure, type 2 diabetes, and/or chronic kidney disease .…”
mentioning
confidence: 99%
See 1 more Smart Citation